Assessing the ecological health of the Chongming Dongtan Nature Reserve, China, using different benthic biotic indices. (September 2019) - Liu, Zhiquan; Fan, Bin; Huang, Youhui; Yu, Ping; Li, Yiming; Chen, Minghai; Cai, Mingqi; Lv, Weiwei; Jiang, Qichen; Zhao, Yunlong
Abstract: To assess the ecological health of the Chongming Dongtan Nature Reserve (CDNR), univariate and multimetric indices—AZTI's Marine Biotic Index (AMBI), multivariate AMBI (M-AMBI), abundance-biomass comparison curves, taxonomic diversity, Shannon-Wiener index ( H ′) (log2 ), and Benthic Opportunistic Polychaetes Amphipods index (BOPA) — were used to translate the macrobenthic community into classifications of ecological health in 2016 and 2017. Based on the results of the various indicators, the overall habitat status of the CDNR ranged from good to high status. Sites 4 and 5, which fell in the remaining tidal flats following reclamation activities, were classified as disturbed, whereas the degree of disturbance at site 3 was low. The results indicate that the CDNR is under some form of human disturbance, which includes reclamation and animal (mainly cattle) grazing. H ′ (log2 ) and M-AMBI index may be more suitable for assessing ecological quality in intertidal zones, including the CDNR. Highlights: The overall ecological status of Chongming Dongtan Nature Reserve was slightly disturbed. Such low disturbance was possibly caused by grazing and reclamation H ′ (log2 ) and M-AMBI indices more suitable for assessing ecological status of intertidal zones